Ivermectin inhibits ER, HER2, and TGF-β pathways in ER-positive and endocrine-resistant breast cancer cells - Kitiya Rujimongkon; Patthamapon Adchariyasakulchai; Chanoknun Boonyaratsewee; Kantasorn Horpratraporn; Wannarasmi Ketchart (PLoS ONE, 2026)
Ivermectin (IVM), initially developed as an antiparasitic drug, has recently demonstrated notable anticancer activity in several malignancies, including breast cancer. Our previous work showed that IVM inhibited cell proliferation and invasion in breast cancer cells, primarily through modulation of the Wnt signaling pathway. Preliminary results further indicated that combining IVM with tamoxifen enhanced its antiproliferative effects in endocrine-resistant breast cancer cells, suggesting a potential role in overcoming drug resistance. To further clarify IVM’s mechanism in the context of endocrine resistance, this study investigated its effects on estrogen receptor-positive (ER⁺) and endocrine-resistant breast cancer cells. IVM significantly suppressed estrogen-induced proliferation and downregulated key resistance-associated markers, including ER and HER2. Additionally, IVM treatment markedly reduced ERK, a downstream effector linked to HER2 and TGF-β signaling. This inhibition was accompanied by a decrease in phosphorylated SMAD2 (pSMAD2) within the TGF-β pathway, while levels of SMAD4—a factor associated with favorable prognosis in endocrine resistance—were maintained. Collectively, these findings highlight IVM’s potential as a repurposed therapeutic agent, with the dual capacity to prevent endocrine resistance in ER⁺ breast cancer and to enhance anti-hormonal therapies in resistant cases.